Peran TNI dalam Penanggulangan Bencana Alam (Studi Kasus Peran Korem 043/Gatam dalam Penanggulangan Bencana Alam di Provinsi Lampung) - Nrangwesthi Widyaningrum; Muhammad Sarip Kodar; Risma Suryani Purwanto; Agung Priambodo; Ifad Fadlurrahman (Universitas Prof. Dr. Hazairin, S.H, 2020)
Abstract Indonesia has the most complete types of disasters in the world such as floods, landslides, tidal waves, tornadoes, drought, forest and land fires, earthquakes, tsunamis, volcanic eruptions, liquefaction and many more. Natural disasters that occur in Indonesia often just happen and it is not predictable when it will happen. This causes problems in handling natural disasters. Natural disaster management is not a matter of BNPB or BPBD, one important element is the involvement of the Indonesian National Army (TNI). One of Indonesia's regions that are vulnerable to natural disasters is Lampung Province. This research will describe how the role of the TNI in the case study in Korem 043 / Gatam in helping to overcome natural disasters in Lampung Province. The research method used in this research is qualitative research with a literature study approach. The role of the TNI in disaster management in Lampung Province is inseparable from the duties and functions of the TNI that have been mandated in Law Number 34 of 2004. Korem 043 / Gatam has taken strategic steps both from the pre-disaster, disaster response, and post-disaster phases . TNI involvement in the process of disaster management does not stand alone, but cooperates and synergizes with local governments.